La teledetección en investigaciones ecológicas como apoyo a la conservación de la biodiversidad: una revisión - Sánchez-Díaz, Baltazar (Revista Científica, 2018)
Currently the most promising application of remote sensing in ecology concerns the field of biodiversity. One of the main threats to biodiversity is the fragmentation and loss of habitat, due to deforestation caused by human activities, accelerating extinction rates in the species. However, biodiversity is difficult to quantify and measure, which is why remote sensing is a valuable tool for ecological research, since, due to its characteristics of spatial, spectral, radiometric and temporal resolution, it is possible to try to measure certain biodiversity variables. However, ecologists and space agencies, in a joint effort, have defined a list of essential variables with which biodiversity can be monitored from space. Due to this, there is a need to use new approaches and tools for its study and conservation, using remote sensing as a tool to support decision-making processes in biodiversity conservation efforts throughout the world.